The Accounting Board and its impact on the quality of financial reports (field study of the Local Administration Directorate of Adrar State 2017-2019) - bendouba, manceur; moumen, abdelkarim (Journal of Research in Finance and Accounting, 2026)
This study aims to search for the Accounting Council and its impact on the quality of financial reports and to achieve the objectives of the study, the researcher adopted the descriptive and analytical approach, and after the field study of the local administration in the state of Adrar, the nature of the expenditures that are considered as the state's running expenditures was reached and we also concluded the extent of the development of these expenditures, especially in recent years. The expenditures of the local administration as part of the public expenditures are subject to financial control, whether tribal, concurrent or subsequent control. As for the postal control represented by the Court of Accounts, there have been many violations and embezzlement by officials on the implementation and rationalization of public expenditures, and there is freedom of access to public orders. Equality is guaranteed with contractors and transparency in procedures. The Board has also recorded the acquisition by two persons of most of the public orders.